(untitled) (Academicia Globe: Inderscience Research, 2023)
One of the social problems that exists in our community is suicidal, or suicide. Problems with the Armed Forces of the Republic of Uzbekistan are part of the public. Because, since the Armed Forces are part of society, there can be no separate existence, aside from these problems. As we all know, the strong socio-political changes that are taking place in the world and society, the development of manufacturing relationships, the development of science and technology, and the rapid entry of them into human life have an impact on a person’s emotional and spiritual condition because these processes are also associated with physical and spiritual abuse (stress). In those who cannot withstand such environments and conditions, a state of stress, crisis (or depression) is causing suicide.